Advances in the Understanding of Reactive Oxygen Species-Dependent Regulation on Seed Dormancy, Germination, and Deterioration in Crops - Li, Wenjun; Niu, Yongzhi; Zheng, Yunye; Wang, Zhoufei (Frontiers in Plant Science, 2022)
Reactive oxygen species (ROS) play an essential role in the regulation of seed dormancy, seed germination and seed deterioration in plants. The low level of ROS as signaling particles promotes dormancy release and triggers seed germination. Excessive ROS accumulation causes seed deterioration during seed storage. Maintaining ROS homeostasis plays a central role in the regulation of seed dormancy, germination and deterioration in crops. This review highlights the current advances on the regulation of ROS homeostasis in dry and hydrated seeds of crops. The research progresses of the crosstalk between ROS and hormones involved in the regulation of seed dormancy and germination are mainly summarized in crops. The current understandings of ROS-induced seed deterioration are reviewed. These understandings of ROS-depended regulation on seed dormancy, germination and deterioration contribute to the improvement of seed quality in the future in crops.